ANALISIS STRATEGI KOMPETITIF SEKOLAH MELALUI PENDEKATAN SWOT DI SMAN 1 PENAJAM PASER UTARA - Rujianto; Aris Ringgi Allo; Kasmal; Evi Susi Sandrawita Br. Saragih; Sandra Dewi; Nurlaili; Usfandi Haryaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the competitiveness of SMAN 1 Penajam Paser Utara using a SWOT approach to identify internal and external strategic factors affecting school development in the buffer zone of Indonesia’s New Capital City (IKN). The research employed a descriptive qualitative approach supported by quantitative analysis using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. Data were collected through interviews, observations, documentation, and questionnaires involving the principal, vice principals, teachers, administrative staff, school committee members, and students. The findings reveal that the school's main strengths include its A accreditation status, qualified teachers, adequate facilities, and strategic location. The major opportunities arise from its proximity to the IKN area, partnerships with various institutions, and advancements in educational technology. The IFAS score was 3.23, while the EFAS score was 2.55. The SWOT coordinate value of (1.97; 0.73) places the school in Quadrant I (Growth-Oriented Strategy), indicating strong internal capabilities and significant external opportunities. The recommended strategy is the SO (Strengths–Opportunities) strategy, which focuses on strengthening partnerships, developing flagship programs, optimizing educational technology, and enhancing the competencies of teachers and students. Nevertheless, the school should continue addressing its weaknesses and mitigating potential threats to sustain its competitiveness and educational quality amid the ongoing development of the IKN region.